Der Fall Max Halbe - Załubska, Cecylia (Studia Germanica Posnaniensia, 2018)
Born in Żulawy near Gdańsk, Max Halbe, a German writer of the turn of the 19th century, was controversial already in his lifetime. He followed the path of an artist whose first work was a success, never matched by his later writings. Often he was forgotten and ignored. Due to his demonstrative aversion to Poles, expressed mainly in his dramas, where it was always the Poles who represented villains, he was much appreciated in the Third Reich. After the Second World War, attempts were made to rehabilitate his good name. Present-day historians of literature have valued him more or less objectively; his contribution to the development of the German naturalism has been acknowledged. However, his anti-Polish attitude has frequently been made no mention of, as has been emphasized in the present article.